웹사이트 사용자 경험 평가에 대한 자기모니터링의 영향 - 김세화(Se-Hwa Kim) (한국콘텐츠학회 논문지, 15(5), 2015)
The following research analyzes that the level of self-monitoring have an influence on user experience about website. For this research, university students participated in a survey where they evaluated user experience -usability, aesthetics, pleasure- about the new screen images of two homepages of differences in brand recognizability. The "self-monitoring(high/low, except for middle)" and the "brand recognizability(high/low, except for middle)" were set as independent variables and the "usability | deviation |", the "aesthetics | deviation |", the "pleasure | deviation |" were set as the dependent variables. Results, as with new screen images of homepage, there were significant differences in the usability and aesthetics based on the level in self-monitoring. Especially, when level of brand recognizability is low, there was more differences in the usability and aesthetics based on the level in self-monitoring. However, the influence of pleasure on self-monitoring was insignificant. 본 연구에서는 웹사이트 사용자 개인의 자기모니터링 수준이 사용자 경험에 미치는 영향을 검증하였다. 조사를 위해 116명의 대학생들에게 사전 지식에 차이가 있는 두 개의 낯선 웹사이트 화면이미지의 사용자 경험(사용성, 심미성, 즐거움 반응)을 측정하였다. 독립변수는 자기모니터링(고/저, 중간 그룹 제외)과 사전지식(고/저, 중간값 제외)이었으며, 종속변수는 사용성 편차, 심미성 편차, 즐거움 편차로 두고 분석하였다. 이때, 편차는 평균으로부터 개인 측정값들 간의 차이를 의미한다. 분석 결과, 낯선 웹사이트 이미지를 볼 때, 자기모니터링 수준이 높은 사람은 자기모니터링 수준이 낮은 사람보다 사용성 편차와 심미성 편차의 차이가 더 컸다. 특히 사전 정보가 적은 경우에서는 자기모니터링 수준에 따라 더 분명한 차이가 나타났다. 그러나 즐거움 평가의 편차에서는 자기모니터링 수준에 따른 차이가 유의미하게 나타나지 않았다.